Evaluación de la incidencia y severidad de trips (Frankliniella occidentalis) con dos métodos de control químico en el cultivo de rosa (Rosa sp.) variedad mondial, en el cantón Cayambe - Guamanquispe Guaman, Edison Daniel (2025)
The rose (Rosa sp.) is a very popular and sought-after ornamental flower in significant events. The incidence and severity of thrips generate high waste of stems, mainly in summer seasons, this condition produces rapid contamination, affecting the quality of the buds, causing deterioration in the physical structure of the plant and does not meet the quality standards for the international market. The research aimed to: Determine the incidence and severity of thrips in rose cultivation; Identify the most effective insecticide for thrips control and establish the benefit-cost ratio of the two types of control. A descriptive and inferential statistical design was used with two treatments, T1 used the insecticide Deltamethrin while T2 used the insecticide Thyocyclam, one experimental unit per treatment and 9 beds per experimental unit. The analysis carried out in this research was a T-test to calculate the % of frequency, maximums, minimums, mean. The variables under study were plant height (PH), bud diameter (BD), bud length (BL), opening diameter (OD), number of main axes (NMA), insecticide efficiency. Taking into account the results, the following conclusions were determined: T1 showed greater thrips infestation in flower buds with an incidence of 5.31% and in plants 2.14%. Compared to T2, it showed 4.01% incidence in buds and 1.30% in plants. However, the severity of the infestation remained low in both cases, classified as grade 2. T2 demonstrated greater chemical efficiency unlike T1, however, T1 proved to be more efficient in economic and agronomic terms. The cost-benefit analysis established that T1 presented a greater source of income, thus obtaining a profit of $1.43 for each dollar invested.